Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
If the derivative of e^x is equal to e^x, why is the derivative of e^x^2 not e^x^2 (why is chain rule used)?
Thanks :)
4 Answers
- ToddLv 61 decade agoFavorite Answer
Technically, the chain rule is used on both of them.
d/dx e^x = e^x * d/dx (x) = e^x * 1 = e^x.
d/dx e^(x^2) = e^(x^2) * d/dx (x^2) = e^(x^2) * 2x.
- Anonymous1 decade ago
Because the outside equation is x^2 and the inside is e^x. Always remember "derivative of the outside leaving the inside alone multiplied by the derivative of the inside. So the derivative of e^x^2 is 2(e^x)(e^x)
- 1 decade ago
because
d/dx e^x = e^x * (x)' = e^x
whereas
d/dx e^x^2 = e^x^2 * (x^2)' = 2x*e^x^2
- harry mLv 61 decade ago
(why is chain rule used) = it's always used
y = e^x
=> dy/dx = e^x * d/dx(x)
=> dy/dx = e^x *1
y = e^5x
=> dy/dx = e^5x * d/dx(5x)
=> dy/dx = e^5x *5
y = e^(x^2 )
=> dy/dx = e^(x^2 ) * d/dx(x^2 )
=> dy/dx = e^(x^2 ) *2x
QED